Hartree–Fock Calculations in Semi-Infinite Matter with Gogny Interactions - Dany Davesne; Alessandro Pastore; Jesus Navarro (Universe, 2023)
Hartree–Fock equations in semi-infinite nuclear matter for finite range Gogny interactions are presented together with a detailed numerical scheme to solve them. The value of the surface energy is then extracted and given for standard Gogny interactions.